Association Between Passive Hip Range of Motion and Pitching Kinematics in High School Baseball Pitchers - Hillary A. Plummer; Nicole M. Bordelon; Kyle W. Wasserberger; Tyler J. Opitz; Adam W. Anz; Gretchen D. Oliver (North American Sports Medicine Institute, 2021)
# Background Limitations in passive hip range of motion (PROM) may negatively affect pitching mechanics in baseball pitchers. Understanding the relationships between PROM and mechanics can assist in the development of injury prevention protocols. # Purpose The purpose of this study was to examine the association of hip rotational PROM with pelvis and trunk rotation during pitching in high school baseball pitchers. Study Design: Cross-sectional. # Methods Twenty-five healthy high school baseball pitchers volunteered (15.9 ± 1.1 years; 180.4 ± 5.5 cm; 75.4 ± 9.3 kg). Seated passive hip internal rotation (IR) and external rotation (ER) PROM were measured using a digital inclinometer. Total PROM was calculated (IR+ER). Pitching biomechanical data were collected with a 3-dimensional electromagnetic tracking system while pitchers threw fastballs. Simple linear regressions were performed to examine the association between hip IR, ER, and total PROM with pitching kinematics at foot contact including stride length, pelvis rotation, and trunk rotation. # Results Only one significant association in PROM and kinematics was observed. Drive leg hip IR PROM was associated with trunk rotation angle [F(1,24) = 4.936, p = 0.036], with an R^2^ = 0.177. Drive leg total PROM was not associated trunk rotation angle [F(1,24) = 4.144, p = 0.053] with an R^2^ = 0.153. # Conclusions Increased drive leg hip IR PROM was associated with decreased trunk rotation towards home plate. Hip total PROM and ER were not related to pitching mechanics. # Level of Evidence 2